PENATAAN KAWASAN JALAN SOMBA OPU SEBAGAI SALAH SATU KAWASAN BERKARAKTER DI KOTA MAKASSAR - Pujantara, Ruly (FORUM BANGUNAN, 2013)
One of the highest activities in city of Makassar is Somba Opu region; this is a preserved and maintained region because of its unique character and its local wisdom. The activity in this region was supporting the improvement of tourism and industrial, so it takes a special treatment and specific arrangement on the design and planning of this region from the point of spatial and architectural perspective. Keywords: spatial planning, Sombaopu region, region characteristic, facade